Evaluation of the Oral Therapy Extension Programme (OTEP) of the Bangladesh Rural Advancement Committee (BRAC): II appendices, January 23 1983-February 22 1983 - Bhatia, Shushum; Cash, Richard A.; Cornaz, Immita (© BRAC, 2016)
1. Abbreviations 2. External evaluation 3. Organization and staff of OTEP 4. Training of OTEP staff 5. The teaching of the families 6. Areas and households covered by OTEP 7. Effectiveness of the teaching and user rates 8. Reported diarrhoea episodes 9. Impact on mortality 10. Security of ORS methods